ISLAMIC PARENTING: AKTUALISASI PENDIDIKAN ISLAM DALAM TAFSIR Q.S. LUQMAN AYAT 12-19 - Abdul Khakim; Miftahul Munir (JIE (Journal of Islamic Education), 2018)
This article discusses the actualization of Islamic education in Islamicparenting in the Luqman family story with the aim of providingexplanations and real solutions to parents about how parents educatechildren by taking the example of family education conducted by Luqman.First, Luqman began his advice to his son by calling for avoiding shirkwhile at the same time containing teachings about the form of the OneGod, because the act of shirk is a great tyranny. Second, worshipeducation, teaches children to worship God by performing prayer as apillar of religion that will help someone from vile and evil deeds. Inaddition to prayer services, parents should also provide their children withinsight into other worship, such as fasting, zakat and pilgrimage. Third,muamalah education, Luqman gave advice to his children to always dogood even though as heavy as mustard seeds, Allah SWT will reciprocate.So also with bad deeds. Fourth, moral education, Luqman teaches childrento be patient and to behave well with fellow human beings, not to lookaway and walk arrogantly (arrogant), to be simple in walking, and tosoften sounds when speaking.